A qualitative exploration of mental health first aid training in underserved communities facing repeated extreme weather events - Adepoju, Omolola E.; De la Roche, Laura; Fuentes, Carlos G.; Tipton, Mary; Suchil, Yahaira (Frontiers in Psychiatry, 2026)
BackgroundSuccessive extreme weather events, including hurricanes and floods, have been reported to negatively impact mental health. Mental Health First Aid (MHFA) training is an evidence-based approach to improve participants’ knowledge, attitudes, and confidence in recognizing, approaching, and supporting individuals experiencing mental health challenges. Investigations have supported its perceived acceptability and utility within professional and health-care populations; however, the appropriateness and applicability of this training in underserved populations in disaster-prone areas are unknown.MethodsEligible participants self-described as residing in disaster-prone areas and participated in MHFA training between February and September, 2025 in Houston, Texas. Individual semi-structured interviews were conducted to assess perceptions of the appropriateness and utility of the MHFA training for disaster preparedness, how participants perceived mental health, and access to available resources 6-8 weeks after the MHFA training completion. Mental health support measures were used to assess the support that participants self-reported they provided to others after completing the MHFA training.ResultsMost participants (63.6%) reported knowing someone who experienced a mental health problem in the past year. Supportive behaviors were common, with over 85% reporting evidence-based responses (e.g., asking about self-harm, active listening, conveying hope, and offering resources). Reflexive thematic analysis resulted in three primary themes: (1) awareness and impact of mental health struggles and the role of the community; (2) understanding the realities of mental healthcare resource access and necessary steps to increase uptake; and (3) community residents indicated the MHFA training was useful and appropriate for disaster preparedness. The findings highlight the usefulness of MHFA trainings in underserved communities that are affected by successive disasters.ImplicationsThe results suggest that MHFA training meaningfully improved participants’ recognition of mental health challenges, confidence in offering support, and awareness of available resources, even within communities facing repeated disaster exposure. These findings also indicate that MHFA may strengthen community capacity for the early identification and response to mental health needs by equipping residents with practical skills that they actively apply in real-world situations following the training.